“So, Why Were You Late Again?”: Social Account’s Influence on the Behavioral Transgression of Being Late to a Meeting - Joseph A. Allen; Emilee Eden; Katherine C. Castro; McKaylee Smith; Joseph E. Mroz (Merits, 2023)
People often offer an excuse or an apology after they do something wrong in an attempt to mitigate any potential negative consequences. In this paper, we examine how individuals employ social accounts when explaining their interpersonal transgression of meeting lateness to others in actual work settings. We examined the different combinations of social accounts and the social outcomes (forgiveness, helping behaviors, and intentions to continue interaction) of being late to a meeting. Across two studies using complementary experimental and survey methods, we found that a majority of late arrivers’ explanations included remorse and that including remorse significantly influences helping behaviors. Furthermore, we found no interaction between excuses and offering remorse. Implications of these findings and future directions are discussed.